Etnopedagogi Pupuh Sunda sebagai Upaya Menumbuhkan Kesadaran Moral Kebhinnekaan pada Siswa Kelas IX di SMPN 1 Tarogong Kidul - Noviana Safitri; Rizky Saeful Hayat; Endang Dimyati; Tetep Tetep; Cecep Kuswara (Cipta Media Harmoni, 2025)
This research is motivated by the importance of instilling diversity values in shaping the moral awareness of students in the midst of multicultural societal conditions. The purpose of this study is to determine the success of the application of Pupuh Sunda ethnopedagogy in increasing moral awareness of diversity values in grade IX C students at SMPN 1 Tarogong Kidul. This study uses the Classroom Action Research (PTK) method with the Kemmis and McTaggart models. The data collection technique is carried out by observation techniques, and test techniques. After the data is obtained, it is analyzed and reflected using the percentage technique. The results of the study show that: 1) Teachers experienced an increase in their ability to design lesson plans in the first cycle reaching a score of 2.50, the second cycle reaching a score of 3.18, and the third cycle reaching a score of 3.77. 2) There is an increase in the moral feeling of diversity of students, the number of students who have not increased (BM) in cycle I, cycle II, and cycle III does not exist. The number of students who began to increase (MM) in the first cycle was 5 children (13.8%), the second cycle there were 15 children (41.6%), and the third cycle there were 19 children (52.7%). The number of children greatly increased (SM) in the first cycle there were 7 children (19.4%), the second cycle there were 12 children (33.3%) and the third cycle there were 18 children (50%). This proves that the application of Pupuh Sunda Ethnopedagogy in PPKn learning can significantly increase the moral feeling of diversity of students.